Front Cover: Validation of the Slow Off‐Kinetics of Sirtuin‐Rearranging Ligands (SirReals) by Means of Label‐Free Electrically Switchable Nanolever Technology (ChemBioChem 8/2020). (24th April 2020) - Schiedel, Matthias; Daub, Herwin; Itzen, Aymelt; Jung, Manfred
Abstract : In residence : The sirtuin rearranging ligands (SirReals) are potent and selective inhibitors of the NAD + ‐dependent lysine deacetylase Sirt2 that induce target rearrangement. Our previous data with a biotinylated probe suggested a slow off‐rate as basis for potency and selectivity. The switchSENSE® technology, which is based on electrically switchable DNA nanolevers, confirmed the findings in a label‐free manner, highlighting its use in analysis of residence time. More information can be found in the full paper by M. Jung et al. on page 1161 in Issue 8, 2020 (DOI: 10.1002/cbic.201900527 ).